Soluble iron inputs to the Southern Ocean through recent andesitic to rhyolitic volcanic ash eruptions from the Patagonian Andes. Issue 8 (7th August 2015) - Simonella, L. E.; Palomeque, M. E.; Croot, P. L.; Stein, A.; Kupczewski, M.; Rosales, A.; Montes, M. L.; Colombo, F.; García, M. G.; Villarosa, G.; Gaiero, D. M.
Abstract: Patagonia, due to its geographic position and the dominance of westerly winds, is a key area that contributes to the supply of nutrients to the Southern Ocean, both through mineral dust and through the periodic deposits of volcanic ash. Here we evaluate the characteristics of Fe dissolved (into soluble and colloidal species) from volcanic ash for three recent southern Andes volcanic eruptions having contrasting features and chemical compositions. Contact between cloud waters (wet deposition) and end‐members of andesitic (Hudson volcano) and rhyolitic (Chaitén volcano) materials was simulated. Results indicate higher Fe release and faster liberation rates in the andesitic material. Fe release during particle‐seawater interaction (dry deposition) has higher rates in rhyolitic‐type ashes. Rhyolitic ashes under acidic conditions release Fe in higher amounts and at a slower rate, while in those samples containing mostly glass shards, Fe release was lower and faster. The 2011 Puyehue eruption was observed by a dust monitoring station. Puyehue‐type eruptions can contribute soluble Fe to the ocean via dry or wet deposition, nearly reaching the limit required for phytoplankton growth. In contrast, the input of Fe after processing by an acidic eruption plume could raise the amount of dissolved Fe in surface ocean waters several times, above the threshold required to initiate phytoplankton blooms. A single eruption like the Puyehue one represents more than half of the yearly Fe flux contributed by dust. Key Points: Patagonian volcanic ashes were evaluated in terms of Fe solubility A single eruption represents about half of yearly Fe flux contributed by dust Effects on the marine primary production of the Southern Ocean are evaluated